Surgical management of abdominal wall sheath and rectus abdominis muscle endometriosis: a case report and literature review - Triantafyllidou, Olga; Mili, Nikoletta; Kalampokas, Theodoros; Vlahos, Nikolaos; Kalampokas, Emmanouil (Frontiers in Surgery, 2024)
Introduction: Endometriosis, defined as the presence of endometrial glands and stroma outside the uterine cavity, mainly affects the pelvic viscera and peritoneum. Endometriosis can also occur at sites of surgical incisions on the abdominal wall, mainly in women with a history of cesarean section (CS). The incidence of abdominal wall endometriosis after CS reaches 1%.Clinical suspicion, along with imaging, plays a crucial role in diagnosis. The preferred treatment involves extensive surgical excision with clear margins, ensuring a definitive diagnosis through histopathology examination.Case Presentation: This case report is of a 44-year-old woman with a history of two CS procedures who developed pain and pigmentation at the incisional site one year after the last CS. Thirteen years after the surgical excision of an abdominal wall endometriosis (AWE) mass, followed by hormone therapy, she presented in our hospital with worsening pain for further management. Pelvic MRI findings were consistent with AWE. During surgery, the abdominal wall endometriosis foci were removed, and the defect in the aponeurosis was repaired using a dual-sided mesh in a tension-free procedure.Although AWE is a rare condition, we foresee an increase in cases because of the ever-increasing CS rates and the important association between AWE and CS. Healthcare practitioners should remain vigilant for this condition in women of reproductive age who exhibit cyclic pain, a palpable mass in the abdomen, and a background of previous uterine surgeries.